Identification of genes involved in male sterility in wheat (Triticum aestivum L.) which could be used in a genic hybrid breeding system. (10th March 2020) - Milner, Matthew J.; Craze, Melanie; Bowden, Sarah; Bates, Ruth; Wallington, Emma J.; Keeling, Anthony
Abstract: Wheat is grown on more land than any other crop in the world. Current estimates suggest that yields will have to increase sixty percent by 2050 to meet the demand of an ever‐increasing human population; however, recent wheat yield gains have lagged behind other major crops such as rice and maize. One of the reasons suggested for the lag in yield potential is the lack of a robust hybrid system to harness the potential yield gains associated with heterosis, also known as hybrid vigor. Here, we set out to identify candidate genes for a genic hybrid system in wheat and characterize their function in wheat using RNASeq on stamens and carpels undergoing meiosis. Twelve genes were identified as potentially playing a role in pollen viability. CalS5‐ and RPG1‐like genes were identified as pre‐ and post‐meiotic genes for further characterization and to determine their role in pollen viability. It appears that all three homoeologues of both CalS5 and RPG1 are functional in wheat as all three homoeologues need to be knocked out in order to cause male sterility. However, one functional homoeologue is sufficient to maintain male fertility in wheat.